Evaluación de la Producción Agroecológica sobre la base de indicadores de sustentabilidad en las Comunidades de Chinaló Bajo e Itualó de la Parroquia Chugchilán, Cantón Sigchos, Provincia de Cotopaxi, 2018. - Feijoo Fernández, Paúl Manuel (2018)
Evaluation of Agroforestry production about sustainable indicators in the communities of Chinaló bajo e Itualó of Chugchilán parish, Cantón Sigchos, Province of Cotopaxi, 2018. The following research evaluated the agroforestry production about sustainable indicators in the Chínalo Bajo e Itualó communities of Chugchilán parish, Cantón Sigchos, Province of Cotopaxi, sustainable indicators were analyzed in the economic, social and environmental which ones allow to know the characteristics of agro-ecological farm. It was elaborated a standardized scale which represents the value of indicators regarding to the current situation using numbering scale from 1 to 4 ddepending on limits assigned for each indicator, 4 is higher the value of sustainability, 3 is medium sustainable, 2 is sustainable value and 1 no sustainable value. To classify the communities that are going to be studied the Sarandón approach was applied with three index of sustainability; A category (very Sustainable), B category (Medium sustainable), C category (Sustainable), and D category (no sustainable). Based on that approach the results gathered were the following; 2.71 Economic dimension (sustainable), 3,44 environmental dimension and 3,17 social dimension both (Medium sustainable). These results showed the production in the communities which were under study are medium sustainable. To calculate the sustainability, the following formula was applied; (GI) general index (GI)= (S+E+E)/D (Social+ Economic+ Environmental/ Dimension) it was gotten general index of 3,10, which means that is Medium sustainable (category B). Finally, it is proposed to do agro-ecological practice such as; soil conservation and the construction of terraces and curved of level, alternate cropping systems and tree planting, fences and windbreakers. Alternate cropping’s according to the year that in cropped and the sequence of time set up, first year tubers, second year legumes, third year vegetables, fourth year grasses. The animal rear must be variable, change animals between, bovine, pigs, guinea pigs, poultry and bees. Vermicompost is also proposed in each of the farms.